Analyzing the Path between the Numbers of Graduates of Education and Unemployment in the Egyptian Economy During the Period (1990 - 2017): Econometrics Analytical Study - Elgafarawe , Enas (The Arab Journal of Administration, 2020)
The current research aims to analyze the path between the numbers of graduates of education and unemployment in the Egyptian economy during the period (1990 - 2017), by using the descriptive approach and the statistical method of multivariate analysis, using the path analysis method, which is a statistical method for testing a model Causal aims to reach quantitative estimates of causal effects, to be used AMOS program to test the paths of the proposed model that shows the direct and indirect causal relationships between the variables forming the model. This is to verify the study hypothesis: Is there a relationship between the unemployment rate in Egypt and each of: the numbers of technical diploma graduates, the numbers of graduates of intermediate and above average education, the numbers of graduates of university education and above university, the rate of population growth, economic growth (represented in per capita Gross domestic product)? The study has been divided into four parts: the theoretical framework of unemployment and its determinants - both ends of the path: unemployment and education outcomes (1990 - 2017) - an analysis of the path between unemployment and its determinants, It concluded that the study hypothesis was accepted for the existence of an inverse relationship between both unemployment U and economic growth Z, while there was a positive relationship between unemployment U and both: population growth rate H, graduates of technical diplomas X1, graduates of intermediate and above intermediate X2 and graduates of university education and above university X3, and there was also a positive relationship Between the intermediate variable represented in the economic growth Z and each of: X1, X2, X3, note that there is a direct impact from the variables X1, X2, X3 on the unemployment variable, as there is an indirect effect of the variables X1, X2, X3 on the unemployment variable through the intermediate variable (Economic growth Z).